Esensi, Hakikat, dan Eksistensi Manusia (Sebuah Kajian Filsafat Islam) - Edi Sumanto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2019)
This paper aims to explore the concept of human philosophy which is an integral part of the philosophical system, which specifically or specifically highlights the nature or essence of human. The method used is analytical descriptive by looking at the opinions of a number of philosophers about human concepts. The results obtained indicate that human essence is material / physical occupy space and time, has breadth and is objective so that it can be measured, calculated, and observed. In terms of its natural position, human beings occupy this position as God's creatures, but they are also beings that can stand on their own, so in fact it can be said that humans have a social nature that can be called "zoon politicon" (the desire to live together). In terms of the nature of human has an individual nature, but this individual also definitely needs help from others.